The Multifunctionality of CD36 in Diabetes Mellitus and Its Complications—Update in Pathogenesis, Treatment and Monitoring - Kamila Puchałowicz; Monika Ewa Rać (Cells, 2020)
CD36 is a multiligand receptor contributing to glucose and lipid metabolism, immune response, inflammation, thrombosis, and fibrosis. A wide range of tissue expression includes cells sensitive to metabolic abnormalities associated with metabolic syndrome and diabetes mellitus (DM), such as monocytes and macrophages, epithelial cells, adipocytes, hepatocytes, skeletal and cardiac myocytes, pancreatic β-cells, kidney glomeruli and tubules cells, pericytes and pigment epithelium cells of the retina, and Schwann cells. These features make CD36 an important component of the pathogenesis of DM and its complications, but also a promising target in the treatment of these disorders. The detrimental effects of CD36 signaling are mediated by the uptake of fatty acids and modified lipoproteins, deposition of lipids and their lipotoxicity, alterations in insulin response and the utilization of energy substrates, oxidative stress, inflammation, apoptosis, and fibrosis leading to the progressive, often irreversible organ dysfunction. This review summarizes the extensive knowledge of the contribution of CD36 to DM and its complications, including nephropathy, retinopathy, peripheral neuropathy, and cardiomyopathy.